Development of Wind and Diesel Generator Hybrid Power System Model for Urban Electrification - Ola Austin Oshin; Engr Olla Moses (Journal La Multiapp, 2022)
The progress and prosperity of any nation depend on the amount of electrical energy consumed in the country. But African countries produce and consume the lowest amount of electricity in the world. This has led to the present incessant, unstable and unreliable power supply system in African Countries which has grounded many activities and has destroyed many industrial processes. This has also increased unemployment rate and increased crime rates in the continents. In order to satisfy the high energy demand in the residential and industrial environments in this continent, and provide solution to these problems, electrical energy should be reliable, aﬀordable, effective, and sustainable.